Engineered Tumor-Derived Extracellular Vesicles: Potentials in Cancer Immunotherapy - Taghikhani, Adeleh; Farzaneh, Farzin; Sharifzad, Farzaneh; Mardpour, Soura; Ebrahimi, Marzieh; Hassan, Zuhair Mohammad (Frontiers in Immunology, 2020)
Exosomes are nano vesicles from the larger family named Extracellular Vesicle (EV)s which are released by various cells including tumor cells, mast cells, dendritic cells, B lymphocytes, neurons, adipocytes, endothelial cells, and epithelial cells. They are considerable messengers that can exchange proteins and genetic materials between the cells. Within the past decade, Tumor derived exosomes (TEX) have been emerged as important mediators in cancer initiation, progression and metastasis as well as host immune suppression and drug resistance. Although tumor derived exosomes consist of tumor antigens and several Heat Shock Proteins such as HSP70 and HSP90 to stimulate immune response against tumor cells, they contain inhibitory molecules like Fas ligand (Fas-L), Transforming Growth Factor Beta (TGF-β) and Prostaglandin E2 (PGE2) leading to decrease the cytotoxicity and establish immunosuppressive tumor microenvironment (TME). To bypass this problem and enhance immune response, some macromolecules such as miRNAs, HSPs and activatory ligands have been recognized as potent immune inducers that could be used as anti-tumor agents to construct a nano sized tumor vaccine. Here, we discussed emerging engineered exosomes as a novel therapeutic strategy and considered the associated challenges.